Inter-Sectoral Cooperation for the Implementation of Social Policy in Rural Areas. Proposal of Research Tool - Katarzyna Zajda; Sławomir Pasikowski (Wieś i Rolnictwo)
The cooperation of local public institutions with non-governmental organisations and citizens can increase chances for the effective implementation of social policy, understood as a set of activities on behalf of satisfying social needs and resolving social issues. The aim of this article is to present a tool that would enable us to determine the level of cooperation between entities in the scope of co-creation and co-production of social services that satisfy the needs of residents of rural municipalities (gmina). The article contains an overview of analyses conducted in 2018 on a sample of public institutions responsible for satisfying social needs and resolving social issues representative of rural municipalities. In light of these analyses the scale is a three-factor construct and includes the following factors: 1. Seeking entities for cooperation and cooperating with them, 2. Including residents of municipalities in undertakings on their own behalf, 3. Evaluation of cooperation and working towards future cooperation.